Analisis Semiotika Visual Orang Desa sebagai Objek Fotografi Okka Supardan - Adhitya Prayoga (Universitas Bumigora, 2022)
Instagram is currently a tool for photography lovers. Many professional photographers use Instagram for their work. One of them was done by a local photographer from Majalengka, West Java, Okka Supardan. Through his Instagram account, Okka tries to present the ins and outs of natural life in the village which he displays through his photograph. This study aims to describe the meaning of photos in Okka Supardan's photography and how the village people are visualized. By using the discourse analysis method, the researcher tries to see and analyze some photos of Okka Suppardan with the semiotic study of Roland Barthes. The results of the study indicate that there is a desire from photographers to show life in the countryside today which has been assimilated with technological attributes that are identical to the times.